Corporate Social Responsibility and Regulatory Initiatives in Turkey: Good Implementation Examples - Gönenç Demir; Melissa N. Cagle; A. Fatih Dalkılıç (Journal of Accounting and Management Information Systems (JAMIS), 2016)
Generally speaking, the integration of stakeholder theory with CSR is fairly well understood. We see that these concepts have, not unlike the development of CSR under the literature, followed a similar vain in Turkey and the current agenda values strong engagement with all stakeholders and advancement of business growth. Especially, within the last decade CSR legislation and requirements have been the topic of extensive discussion. Turkey has seen an influx of activity and increasing pressure to further the CSR agenda and has gathered the backing of various events and organizations. In light of these developments, we attempt to explore the current social and economic environment within the country in regards to CSR practices. In this study, we offer detailed descriptions of the relevant CSR national laws and regulations on e.g. labour practices, human rights and environment and explore the current CSR reporting practices while offering descriptive evidence on the trend and future direction for CSR reporting statistics in Turkey.
Keywords: K22; M14; M21; 650; Corporate Social Responsibility; Regulation; Institutional Structure; Stakeholders; Turkey